Banks’ loan charge-offs and macro-level risk - Jin, Justin; Ma, Mary L. Z.; Song, Victor; Guo, Mengyang; Michael Lee-Chin & Family Institute for Strategic Business Studies (My University, 2021)
Prior studies document that delayed loan loss provisions can worsen financial stability by triggering a capital inadequacy concern. We extend prior literature and investigate how the treatment of loan charge-offs (LCOs) in financial statements is tied to macro-level risk in the U.S. banking industry. We hypothesize and find that nondiscretionary LCOs are positively linked to banks’ future systemic risk, whereas discretionary LCOs are negatively correlated with banks’ future systemic risk. We further show that these effects are driven by two economic mechanisms: banks’ common risk exposure and interconnectedness. This study is the first to document the linkage between banks’ discretionary LCOs and macro-level risk in the banking industry. Valuation Insight: Bank loan charge-offs are found to anticipate systemic risk: discretionary loan charge-offs negatively forecast systemic risk of the banking sector; nondiscretionary loan charge-offs positively forecast systemic risk. The valuation of a typical bank may price in the systemic risk, depending positively (negatively) on the aggregate discretionary (nondiscretionary) loan charge-offs in the banking sector.
62 p. ; Includes bibliographical references (pp. 58-62) ; March 5, 2021.
Keywords: Banks; Financial statements; Loan charge-offs; Systemic risk; Macroeconomy